Pesantren dan Konflik Keluarga: (Studi Kasus Pesantren Alfadiliyah Ciamis) - Aripudin, Acep (Jurnal Ilmu Dakwah, 2012)
The fall of pesantren have been many differents problem one and the other. In the case of Alfadiliyah in this research has been many problems: first, leadership factor, which the successor of kyai leadership from old leaders to present has not followed normally method in generally tradisional pesantren; second, there are reformation movement on understanding and tradisional practices of culture pesantren which done by generation leader pesantren after die founder. Reformation Â movement like it mede opportunity to struggle from internal leader family, so stimulating struggle and conflict in pesantren; third, genetical factor as the influenced situation from many problems is competition in to pesantren assets, like materials, roles and power.